Method of discussion and learning styles towards student's critical thinking ability - A. Jauhar Fuad (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
Active learning with student centering can improve critical thinking skills. Debates and discussions encourage active learning. Both are oriented toward critical thinking ability, in addition to the learning styles also make an impact on critical thinking ability. This paper aims to answer whether there are (1) differences in students critical thinking ability in the debate class and discussion class, (2) differences in critical thinking ability of students who have divergent learning styles and convergent learning style, and (3) interaction between learning method and learning style to critical thinking ability? This study uses a pseudo experimental design. Subjects in this study are students semester II. Analytical technique using Anova. The results of this study conclude: (1) there is no difference in critical thinking ability between debating class and discussion class, (2) there is difference of critical thinking ability between convergent learning style and divergent learning style, convergent learning style is better than divergent learning style, and (3) there is interaction between learning method and learning style to critical thinking ability which means that the influence of learning method on critical thinking ability is influenced by learning style.